2022
DOI: 10.2172/1893370
|View full text |Cite
|
Sign up to set email alerts
|

EvaluateFlux, VARPOW, VARPEAK, and DIF3DtoVTK Utility Programs for DIF3D

Abstract: The DIF3D-VARIANT solver is part of the DIF3D code which was developed at ANL for engineering level predictive analysis of nuclear reactor cores. Over the course of the last 20 years, the DIF3D-VARIANT option of DIF3D has become increasingly more used because of improvements in computer memory capabilities and performance. This is beneficial to the users of DIF3D as DIF3D-VARIANT is able to apply both p-and h-spatial mesh refinement strategies in diffusion and transport theory. Given its greater use, utility p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The PMATRX, ISOTXS, LABELS, GEODST, NDXSRF, ZNATDN, NHFLUX, and GHFLUX files are all interface files generated by the Argonne codes DIF3D, MC 2 -3, REBUS, and GAMSOR. A detailed description of each input can be found in the VARPOW user manual [1] with test cases in [10], and so further discussion is not necessary here. All of the other input options shown in Figure 2 must be verified as part of this work.…”
Section: Varpow Inputs and Outputs To Verifymentioning
confidence: 99%
See 3 more Smart Citations
“…The PMATRX, ISOTXS, LABELS, GEODST, NDXSRF, ZNATDN, NHFLUX, and GHFLUX files are all interface files generated by the Argonne codes DIF3D, MC 2 -3, REBUS, and GAMSOR. A detailed description of each input can be found in the VARPOW user manual [1] with test cases in [10], and so further discussion is not necessary here. All of the other input options shown in Figure 2 must be verified as part of this work.…”
Section: Varpow Inputs and Outputs To Verifymentioning
confidence: 99%
“…In summary, the neutron and gamma heating distributions are given in either two or six components, with the option to be normalized or unnormalized, by choosing one of the four options. Initial testing between two-and six-component cases showed that the temperature distribution impact was in the fourth significant digit (a sodium cooled, metal fueled fast reactor), showing minimal advantage in using the six-component option [1]. Further, DASSH prefers to use normalized results so that it does not need to needlessly normalize the results itself when running, so option M is recommended for DASSH applications.…”
Section: Varpow Inputs and Outputs To Verifymentioning
confidence: 99%
See 2 more Smart Citations
“…The Argonne Reactor Code (ARC) software suite [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] has been developed by Argonne researchers for fast reactor design and analysis since the 1970s. With the ARC software suite, a user can quickly build a model of a proposed or existing fast spectrum reactor and carry out fuel cycle, nominal thermal analysis and flow requirements, and assess, as is appropriate, whether the core design and constraint system yield an acceptable mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%